Cone-beam computed tomography-guided online adaptive radiotherapy is feasible for prostate cancer patients - Zwart, Lisanne G.M.; Ong, Francisca; ten Asbroek, Liselotte A.; van Dieren, Erik B.; Koch, Siete A.; Bhawanie, Anand; de Wit, Elisabeth; Dasselaar, Judith J. (Physics and imaging in radiation oncology, 2022)
•Online adaptive radiotherapy (oART) is achievable within twenty minutes.•Cone-beam computed tomography-guided oART is feasible in daily clinical practice.•The adapted plan was always preferred over the scheduled plan. Studies have shown the potential of cone-beam computed tomography (CBCT)-guided online adaptive radiotherapy (oART) for prostate cancer patients in a simulation environment. The aim of this study was to evaluate the feasibility of the clinical implementation of CBCT-guided oART for prostate cancer patients. Between February and July 2020, eleven prostate cancer patients were treated with CBCT-guided oART using a fractionation scheme of 20 × 3 Gy to the prostate and 20 × 2.7/3.0 Gy to the seminal vesicles for more advanced stages. The on-couch adaptive workflow consisted of influencer (prostate, seminal vesicles, rectum, bladder) review, target review, scheduled (re-calculated) and adapted (re-optimized) plan generation, an independent QA procedure and treatment delivery. Treatment time, proportion of adapted fractions and reasons for plan adaptation were evaluated. Mean total treatment time (±SD) from CBCT acquisition to end of treatment delivery was 17.5 ± 3.2 min (range: 10.8–28.8 min). In all 220 fractions, the PTV coverage was increased for the adapted plan compared to the scheduled plan. The V60Gy of bladder and rectum were below the constraints (<5% and <3%) for both scheduled and adapted plans in 171 out of 220 fractions and for the adapted plan only in 30 out of 220 fractions. In 19 out of 220 fractions, the V60Gy of the bladder and/or rectum was above the constraint for the adapted plan. The clinical implementation of CBCT-guided oART is feasible for prostate cancer patients. The adaptive workflow is possible within twenty minutes on average with a dedicated team.